Professional-oriented reading at university: actual issues - Лєшньова, Н. О.; Павлова, Л. В.; Сергеєва, О. А. (Scientific notes of the pedagogical department, 2019)
Reading is a universal and convenient means of obtaining the necessary information. Modern students have to read a large number of texts in foreign languages to obtain the necessary informa-tion from various fields of knowledge. A methodological system of studying at an institution of higher education that is unable to give proper reading skills cannot be considered effective and rational one. The purpose of the study is to consider reading as one of the main foreign language teaching strategies at an institution of higher education and determine the most effective types of reading at non-linguistic faculties in the context of reducing classroom hours, as well as, to determine the most appropriate teaching materials for successful realizing students’ reading skills. Reading is one of the receptive types of speech activity since it relies on the perception (recep-tion) of information within a written text. It includes techniques of reading and understanding. Combining two kinds of reading: analytical (based on training texts and performed mainly in classes) and extensive (outside the classroom) is the most effective approach. A training text is one of the main tools for forming and developing students’ reading skills and the ability to process different types of training texts and advances the ability to speak on profession-al-oriented topics. Taking into account the fact that students’ knowledge of foreign languages varies widely, the text selection should be guided by one of the didactic principles – the principle of accessibility, which is reflected both in the content of the texts and in the lexical means that convey this content. At university scientific texts should be preferred as training ones, due to their main features, namely, logicality and lack of emotionality. The text, its content and reading strategies, which match the individual abilities of students and the arsenal of their knowledge of both the foreign language and the specialty, are essential means of controlling the student’s motivation.